Objektiver und absoluter Geist nach Hegel: Kunst, Religion und Philosophie innerhalb und außerhalb von Gesellschaft und Geschichte - Oehl, Thomas; Kok, Arthur; Hegel, Georg Wilhelm Friedrich (Critical studies in German idealism, 2018)
Thomas Oehl and Arthur Kok offer an extensive selection of papers exploring the wide spectrum of Hegel?s philosophy of spirit from the viewpoint of the distinction between objective and absolute spirit. Challenging Hegelianism?s current tendency to reduce absolute spirit to objective spirit, the editors have invited a large number of highly-esteemed Hegel scholars to reflect about the domains of absolute spirit (art, religion and philosophy) and their relation to society and history, thereby addressing the universal issue about whether there are cultural phenomena which transcend society and history anew from a Hegelian perspective
Literaturverzeichnis: Seiten 900-926
Keywords: Hegel, Georg Wilhelm Friedrich -- 1770-1831; Aufsatzsammlung; Ästhetik; Hegel, Georg Wilhelm Friedrich; Religionsphilosophie; Politische Philosophie; Rechtsphilosophie; Philosophie; Begriff; Geist